The renaissance of Roman colonization : Carlo Sigonio and the making of legal colonial discourse - Pelgrom, Jeremia; Weststeijn, Arthur (Oxford : Oxford University Press, 2020)
Bringing together experts on Roman history, the history of classical scholarship, and the history of international law, this text analyzes the context, making, and impact of the great Italian Renaissance scholar Carlo Sigonio (1522/3-84) and his reconstruction of the Roman colonial model.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 4, 2020).
Keywords: Sigonio, Carlo, -- 1524?-1584.; Rome -- Colonies -- Italy; Local government -- Rome; Roman law; Europe -- Civilization -- Roman influences